1996
DOI: 10.1034/j.1600-0870.1996.t01-2-00001.x
|View full text |Cite
|
Sign up to set email alerts
|

A case study of a severe Adriatic bora on 28 December 1992

Abstract: Most bora research, until now, considered the appearance of the severe bora only on the northern Adriatic. However, the important topic of this paper is the internationally less known southern Adriatic bora. Preliminary results, including ours, begin to change the traditional view of bora as a local small‐scale phenomenon by suggesting that bora‐related airflow has a multi‐scale nature. Here, we present a rare synoptic situation which was characterized by the strong NE flow through the entire depth of the trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…In the case of weak upstream flow it was found that the factor contributing most to the development of pronounced lee slope winds is wave overturning which occurs beneath the inversion layer [ Jurčec and Glasnović , 1991]. Evidence has been found both against [ Ivančan‐Picek and Tutiš , 1996] and for simple hydraulic theory [e.g., Bajić , 1991; Vučetić , 1993]. Lazić and Tošić [1998] used real data simulation to investigate the influence of mountain height on bora trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of weak upstream flow it was found that the factor contributing most to the development of pronounced lee slope winds is wave overturning which occurs beneath the inversion layer [ Jurčec and Glasnović , 1991]. Evidence has been found both against [ Ivančan‐Picek and Tutiš , 1996] and for simple hydraulic theory [e.g., Bajić , 1991; Vučetić , 1993]. Lazić and Tošić [1998] used real data simulation to investigate the influence of mountain height on bora trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…This might also be a partial explanation for the spatial variability of the bora wind along the eastern Adriatic coast (e.g. Ivancan-Picek and Tutiš 1996;Brzovic 1999) in addition to the upstream flow preconditioning.…”
Section: (B) Backgroundmentioning
confidence: 99%
“…Several authors have stressed the need to consider a three-dimensional view of the bora in order to explain the local differences of its structure (e.g. Glasnović and Jurčec 1990;Jurčec and Glasnović 1991;Ivančan-Picek and Tutiš 1996). Three-dimensional numerical case-studies with horizontal model mesh sizes larger than 5 km (Lazić and Tošić 1998;Tošić and Lazić 1998;Qian and Giraud 2000;Morelli and Berni 2003) revealed, for example, preferred regions with severe bora winds.…”
Section: Introductionmentioning
confidence: 99%